Broccoli, Raab—Brassica rapa L. (Ruvo group) - James M. Stephens (EDIS)
This document provides detailed information on broccoli raab (Brassica rapa L.), a vegetable grown for its tender leaves and flower shoots. The document covers the plant's description, cultivation practices, and harvesting methods. Broccoli raab is typically planted in fall, winter, or early spring, with specific strains suited for different planting seasons. The document also includes preparation tips, highlighting its sharp taste similar to broccoli. Original publication date April 1994.